Natural Disasters and Rural Vietnam: Estimations and Forecasts - Tam, Bang Vu (University of Economics Ho Chi Minh City, 2023)
Using disaster data from the emdat.be website and data for six regions in Vietnam, this paper investigates the impacts of natural disasters on the gross product per capita of the three rural sectors that have been affected the most by disasters―agriculture, fishery, and forestry―over the period 1995 to 2013. The preliminary tests reveal endogeneity and contemporaneous correlations among these three sectors. Hence, a combination of instrumental variable (IV) estimations and system seemingly unrelated regressions (SSUR) are employed. The results reveal that disasters have different impacts on different sectors of the rural Vietnam with agriculture suffering the heaviest losses, fishery second, and forestry suffers the least. We then analyze the effects of reforestation as a disaster prevention measure and provide forecasts on the forest development in Vietnam.